The Impact of Game-Based Learning (GBL) on Students’ Motivation and Productive Skills Ways and Challenges of Integrating Games within the EFL Classroom - AMARA, NOAMEN (2024)
The dissertation is about the importance of Game-based learning as a teaching strategy to improve learners' productive skills in English as a foreign language.